Implementación de laboratorio para el estudio y diseño de radio enlaces de microondas digitales en la Universidad Antonio Nariño sede Ibagué utilizando tecnología Airmax ac de Ubiquiti. (2020)
This project carries out the implementation of the necessary infrastructure that allows the analysis, study and design of a radio link between the microwave bands and thus contribute to promoting the development of the telecommunications area in the electronic engineering.